Leaving Cold Sassy - Burns, Olive Ann (Ticknor and Fields, 1992)
Fifteen chapters of an unfinished sequel to the best-selling novel Cold Sassy Tree are drawn to a conclusion by Burns's editor who also reflects on the inspiring life of Olive Ann Burns.
64189
Keywords: Fiction; Family Life Fiction